2012
DOI: 10.1139/b2012-015
|View full text |Cite
|
Sign up to set email alerts
|

Histological and anatomical responses in avocado, Persea americana, induced by the vascular wilt pathogen, Raffaelea lauricola

Abstract: Raffaelea lauricola causes laurel wilt of avocado, Persea americana. Host × pathogen interactions were examined with light and scanning electron microscopy. The susceptible avocado cultivar 'Simmonds' was inoculated and examined 5 cm above the inoculation site 3, 7, 14, 21, and 42 days after inoculation (dai). No external symptoms were observed at 3 and 7 dai, and there were no anatomical differences when compared with the mock-inoculated plants. By 14 dai, external symptoms were present and dark discoloration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 27 publications
(50 reference statements)
0
39
0
Order By: Relevance
“…This results in the plugging of water‐conducting tissues and wilt symptoms, presumably by the fungal tissues as well as by the production of tyloses and gums by the host (Inch and Ploetz ; Inch et al. ). Later generations of beetles make brood galleries in the wilted trees (Harrington and Fraedrich ).…”
Section: Introductionmentioning
confidence: 99%
“…This results in the plugging of water‐conducting tissues and wilt symptoms, presumably by the fungal tissues as well as by the production of tyloses and gums by the host (Inch and Ploetz ; Inch et al. ). Later generations of beetles make brood galleries in the wilted trees (Harrington and Fraedrich ).…”
Section: Introductionmentioning
confidence: 99%
“…After laurel wilt-susceptible (avocado and swamp bay) and tolerant (camphortree) hosts were inoculated with a green fluorescent protein (GFP)-labelled strain of R. lauricola, Campbell et al [120] reported that the pathogen was scarcely visible in microscopic cross sections, even in dead or dying plants. Although they observed that a maximum of 0.9% of the xylem lumena of avocado were colonized by the GFP-labelled strain 30 days after inoculation (dai) (Figure 4), about 40% of the lumena of avocado were occluded by tyloses 21 dai in another study [123] (Figure 5). Mobility of the pathogen or its metabolites in the xylem seems to be related to susceptibility.…”
Section: Host Responses To Infection By Raffaelea Lauricolamentioning
confidence: 93%
“…To date, we have only rudimentary understandings of these processes [33,[121][122][123]. Although natural selection against susceptibility has probably occurred in camphortree and other Asian Lauraceae [1,33], host attributes that are associated with laurel wilt tolerance have been studied only recently [121].…”
Section: Hosts Of Laurel Wiltmentioning
confidence: 99%
See 1 more Smart Citation
“…Harr., Fraedrich & Aghayeva (Ophiostamatales: Ophiostomataceae), causes laurel wilt [5]–[6]. The presence of R. lauricola in susceptible hosts elicits a cascade of events, including secretion of resins and formation of extensive parenchymal tyloses that wall off conductive xylem vessels [7][8]. This defensive response results in diminished water transport, which initially impedes spread of the mycopathogen, but ultimately leads to systemic wilt and host tree mortality.…”
Section: Introductionmentioning
confidence: 99%